Environmental Heterogeneity Determines Diatom Colonisation on Artificial Substrata: Implications for Biomonitoring in Coastal Marine Waters - Cotiyane-Pondo, Phumlile; Bornman, Thomas G. (Frontiers in Ecology and Evolution, 2021)
Benthic diatoms form an important component of the microphytobenthos and have long been utilised as suitable bioindicators in aquatic systems. However, knowledge on benthic diatom community succession on hard substrata (biofilm) remains understudied in austral marine coastal systems. In this study, we investigated benthic diatom colonisation on artificial substrates (Plexiglass) over a period of five weeks at two locations with different physical environments along the warm temperate coast of South Africa. Results revealed relatively similar physico-chemical conditions but highly contrasting diatom community development were observed between the two sites. While there were some shared taxa, site-specific dynamics resulted in significantly different diatom species diversity and richness, facilitated by common (e.g. Nitzschia ventricosa and Cocconeis scutellum) and a large percentage of rarely observed species such as Cocconeis testudo and Lyrella lyra. A total of 134 species belonging to 44 genera were observed during the study. The overall diatom composition differed spatio-temporally during the experimental period, with the fluctuating species occurrences and abundances highlighting the rapid microalgal species turnover under natural conditions. Environmental variables were shown to have varying influences as drivers of the diatom community descriptors. Multivariate modelling confirmed that study site and the interaction between site and sampling occasion were important predictors of diatom abundances, and the overall observed community composition. The current results suggest that benthic diatoms on artificial substrata could be incorporated as suitable indicators of change along the coastline subject to further investigations, taking into account site-specific differences driven by habitat complexity and environmental variability. The experimental method proved to be efficient and can be implemented to study the response of benthic diatoms to localised nutrient enrichment around the coastline